The effects of income and inflation on financial development: Evidence from heterogeneous panels - Kizito Uyi Ehigiamusoe; Vinitha Guptan; Suresh Narayanan (Kiel Institute for the World Economy (IfW), 2019)
This paper examines four unresolved issues regarding the effects of GDP and inflation on financial development: (i) Does GDP have uniform impact on financial development in heterogeneous income countries? (ii) Is the relationship non-linear? (iii) Does financial development vary with inflation rates? (iv) Does inflation moderate the effect of GDP on financial development? The authors employ the newly developed dynamic Common Correlated Effects (CCE) and dynamic panel system Generalized Method of Moments (GMM) on data from 125 countries. These techniques enable us to control for crosssectional dependence, heterogeneity and endogeneity. They show that GDP has a positive impact on financial development in high and middle-income countries, and the relationship is non-linear in over 60% of the countries. The authors also reveal that inflation has a negative effect on financial development in high- and medium-inflationary countries. Besides, high inflation moderates the effect of GDP on financial development in over 70% of the countries. They also show the countries where higher GDP is better for financial development and where it is not. They recommend some policy options based on the findings.
Keywords: G15; F10; E31; 330; financial development; income; inflation rate